Security of key infrastructure that provide vital activity of population and national economy in emergency cases (in domestic armed conflict) - Dovbnya, V. V.; Amelin, Yе. L. (Honor and Law, 2019)
A problem concerning security of key infrastructure that provide vital activity of population and national economy in emergency cases and duties of a unit commander under these conditions are considered.